Adapting Global ELT Syllabuses for Local Needs in Indonesian Secondary Schools - Kalayo Hasibuan; Allya Ramadhani; Chelsea Nuralya; Ashabu Thifla Al Fuadi (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
The use of global English language teaching (ELT) syllabuses in Indonesian secondary schools often creates problems because the content and examples do not always match students’ cultural contexts and learning needs. This qualitative, descriptive literature review examines how globally designed ELT syllabuses are adapted for Indonesian classrooms. Drawing on fifteen Scopus-indexed studies published between 2020 and 2025, including works by Zein et al. (2020), Hanifa et al. (2024), Nurteteng et al. (2024), Fudiyartanto (2024), and Al Fikri (2025), the review identifies common adaptation strategies, challenges, and resulting teaching practices. Findings show that teachers frequently modify global syllabuses by adjusting cultural content and simplifying language to fit local realities (Hanifa et al., 2023; Andriani, 2024). However, obstacles remain, such as limited school support, insufficient teaching materials, and mismatches between curriculum demands and school policies (Nurteteng et al., 2024; Pajarwati, 2021). Although previous studies provide useful insights, most fail to offer concrete models for adapting global ELT materials to Indonesia’s Merdeka Curriculum, highlighting the need for further research.